2011
DOI: 10.1039/c0ja00108b
|View full text |Cite
|
Sign up to set email alerts
|

Determination of trace metals in high-salinity petroleum produced formation water by inductively coupled plasma mass spectrometry following on-line analyte separation/preconcentration

Abstract: A procedure is detailed for the determination of trace metals in high salinity petroleum produced formation water (PFW) by inductively coupled plasma mass spectrometry (ICP-MS) coupled with flow injection (FI) on-line matrix separation and preconcentration. High salinity PFW waters present complex composition containing various organic and inorganic substances. Mini-columns packed with Toyopearl AF-Chelate-650M iminodiacetate resin were used for the analyte separation/ preconcentration of Cd, Pb, Ni, Zn, V, Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Among the extraction techniques currently being used for the preconcentration of Cd (II) are solid phase extraction (SPE) (Lemos, Bezerra, & Amorim, 2008;Oliveira et al, 2011), cloud point extraction (CPE) (Arain et al, 2014), liquideliquid extraction (LLE) (Mellah & Benachour, 2006), and coprecipitation (Prasad, Gopikrishna, Kala, Rao, & Naidu, 2006). Recently, the need for the development of rapid, simple, and versatile methods has led to the miniaturization of some extraction techniques, for example solidphase microextraction (SPME) (Tian, Cheng, Ye, Liu, & Jia, 2014) and liquid-phase microextraction (LPME) (Cunha & Fernandes, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Among the extraction techniques currently being used for the preconcentration of Cd (II) are solid phase extraction (SPE) (Lemos, Bezerra, & Amorim, 2008;Oliveira et al, 2011), cloud point extraction (CPE) (Arain et al, 2014), liquideliquid extraction (LLE) (Mellah & Benachour, 2006), and coprecipitation (Prasad, Gopikrishna, Kala, Rao, & Naidu, 2006). Recently, the need for the development of rapid, simple, and versatile methods has led to the miniaturization of some extraction techniques, for example solidphase microextraction (SPME) (Tian, Cheng, Ye, Liu, & Jia, 2014) and liquid-phase microextraction (LPME) (Cunha & Fernandes, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Table 6 it is observed that the trace metal levels in the production formation waters analyzed did not exceed the Brazilian guidelines. The proposed method allows determining these five metals in lower limit of quantification than other methods previously published [4,28,30]. Also an online solid-phase extraction offers some additional advantage, in comparison to other methods, such as reutilization of solid phase for several cycles, simplicity, elimination of matrix effect, and low reagent consumption.…”
Section: Applicationmentioning
confidence: 84%
“…It is a practice throughout the oil industry, physically separating water from fluids and then discard them directly into the ocean or injecting it back into the wells or other suitable geological formations, with or without further treatment. 2 The PFW is a complex mixture constituting of the injection water, hydrocarbons residual, metals in the form of inorganic salts, radioactive materials and chemical residues added during the production and treatment process in the extraction.…”
Section: Introductionmentioning
confidence: 99%